Chemical constituents and bioactivity of Curcuma aeruginosa Roxb - Sukari, Mohd Aspollah; Md Saad, Suhaila; Lajis, Md Nordin; Rahmani, Mawardi; Muse, Radzali; Yusuf, Umi Kalsum; Riyanto, Sugeng (Korean Society of Pharmacognosy, 2007)
Phytochemical study on the rhizomes of Curcuma aeruginosa has yielded three sesquiterpenes, which were identified as zedoarol (1), curcumenol (2) and isocurcumenol (3). The structures of the compounds were determined by Infrared Spectroscopy (IR), Nuclear Magnetic Resonance (1D and 2D NMR) and Mass Spectroscopy (MS). The crude extracts and pure compounds obtained were tested against pathogenic microbes and cancer cell lines.